Question
upstudy study bank question image url

d) \( x^{2}-7 x+6 \) f) \( x^{2}-2 \frac{1}{5} x+\frac{2}{5} \) h) \( 2 x^{2}-11 x+5 \)

Ask by Patel Cook. in South Africa
Feb 19,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are: - \( x = 1 \) and \( x = 6 \) for \( d) \) - \( x = \frac{1}{5} \) and \( x = 2 \) for \( f) \) - \( x = \frac{1}{2} \) and \( x = 5 \) for \( h) \)

Solution

Solve the quadratic equation by following steps: - step0: Solve by factoring: \(x^{2}-7x+6=0\) - step1: Factor the expression: \(\left(x-6\right)\left(x-1\right)=0\) - step2: Separate into possible cases: \(\begin{align}&x-6=0\\&x-1=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=6\\&x=1\end{align}\) - step4: Rewrite: \(x_{1}=1,x_{2}=6\) Solve the equation \( 2 x^{2}-11 x+5=0 \). Solve the quadratic equation by following steps: - step0: Solve by factoring: \(2x^{2}-11x+5=0\) - step1: Factor the expression: \(\left(x-5\right)\left(2x-1\right)=0\) - step2: Separate into possible cases: \(\begin{align}&x-5=0\\&2x-1=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=5\\&x=\frac{1}{2}\end{align}\) - step4: Rewrite: \(x_{1}=\frac{1}{2},x_{2}=5\) Solve the equation \( x^{2}-2 \frac{1}{5} x+\frac{2}{5}=0 \). Solve the quadratic equation by following steps: - step0: Solve by factoring: \(x^{2}-2\frac{1}{5}\times x+\frac{2}{5}=0\) - step1: Convert the expressions: \(x^{2}-\frac{11}{5}x+\frac{2}{5}=0\) - step2: Factor the expression: \(\frac{1}{5}\left(x-2\right)\left(5x-1\right)=0\) - step3: Divide the terms: \(\left(x-2\right)\left(5x-1\right)=0\) - step4: Separate into possible cases: \(\begin{align}&x-2=0\\&5x-1=0\end{align}\) - step5: Solve the equation: \(\begin{align}&x=2\\&x=\frac{1}{5}\end{align}\) - step6: Rewrite: \(x_{1}=\frac{1}{5},x_{2}=2\) Let's solve each of the quadratic equations step by step. ### d) \( x^{2}-7x+6 = 0 \) To solve this equation, we can factor it: \[ x^{2}-7x+6 = (x-1)(x-6) = 0 \] Setting each factor to zero gives us: 1. \( x - 1 = 0 \) → \( x = 1 \) 2. \( x - 6 = 0 \) → \( x = 6 \) Thus, the solutions are: \[ x_{1} = 1, \quad x_{2} = 6 \] ### f) \( x^{2}-2\frac{1}{5}x+\frac{2}{5} = 0 \) First, let's convert \( 2\frac{1}{5} \) to an improper fraction: \[ 2\frac{1}{5} = \frac{11}{5} \] Now, the equation becomes: \[ x^{2} - \frac{11}{5}x + \frac{2}{5} = 0 \] Using the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \): - \( a = 1 \) - \( b = -\frac{11}{5} \) - \( c = \frac{2}{5} \) Calculating the discriminant: \[ b^2 - 4ac = \left(-\frac{11}{5}\right)^2 - 4 \cdot 1 \cdot \frac{2}{5} = \frac{121}{25} - \frac{8}{5} = \frac{121}{25} - \frac{40}{25} = \frac{81}{25} \] Now, substituting into the quadratic formula: \[ x = \frac{\frac{11}{5} \pm \sqrt{\frac{81}{25}}}{2} = \frac{\frac{11}{5} \pm \frac{9}{5}}{2} \] This gives us two solutions: 1. \( x = \frac{20/5}{2} = 2 \) 2. \( x = \frac{2/5}{2} = \frac{1}{5} \) Thus, the solutions are: \[ x_{1} = \frac{1}{5}, \quad x_{2} = 2 \] ### h) \( 2x^{2}-11x+5 = 0 \) Using the quadratic formula again: - \( a = 2 \) - \( b = -11 \) - \( c = 5 \) Calculating the discriminant: \[ b^2 - 4ac = (-11)^2 - 4 \cdot 2 \cdot 5 = 121 - 40 = 81 \] Now substituting into the quadratic formula: \[ x = \frac{11 \pm \sqrt{81}}{4} = \frac{11 \pm 9}{4} \] This gives us two solutions: 1. \( x = \frac{20}{4} = 5 \) 2. \( x = \frac{2}{4} = \frac{1}{2} \) Thus, the solutions are: \[ x_{1} = \frac{1}{2}, \quad x_{2} = 5 \] ### Summary of Solutions - For \( d) \): \( x_{1} = 1, \quad x_{2} = 6 \) - For \( f) \): \( x_{1} = \frac{1}{5}, \quad x_{2} = 2 \) - For \( h) \): \( x_{1} = \frac{1}{2}, \quad x_{2} = 5 \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

Let's shake things up a bit and delve into some fascinating tidbits! Did you know that the quadratic formula, which helps solve equations like these, has been around since ancient civilizations? The Babylonians were actually solving quadratic equations around 2000 BC! They may not have had fancy variables like \(x\), but their methods laid the groundwork for what we use today. Now, onto practical applications! Quadratic equations aren't just for math classrooms—they pop up in real life, too! From optimizing profit margins in business to calculating the trajectory of a basketball during a shot, these equations help us analyze situations and make informed decisions. So next time you see a parabola, remember it has a real-world purpose beyond homework!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy